Building Educational Relationships between Teachers and Students from the Perspective of KH. Hasyim Asy’ari: A Literature Review of the Book Adab Al-'Alim Wa Al-Muta'allim - Sakdiah, Halimatus; Matsum, Hasan (STAI Serdang Lubuk Pakam, 2025)
The relationship between teachers and students is an educational bond grounded in specific norms to achieve learning objectives. KH. Hasyim Asy’ari, as a prominent figure in Islamic education in Indonesia, devoted significant attention to this aspect, particularly through his work Adab al-‘Alim wa al-Muta‘alim. This study aims to describe the teacher–student relationship from KH. Hasyim Asy’ari’s perspective, focusing on his thoughts regarding the role of teachers, the role of students, the nature of their relationship, and its relevance to contemporary education. The research employs a library research method by examining primary literature as well as previous studies. The findings reveal that KH. Hasyim Asy’ari emphasized the importance of moral and spiritual cultivation, teachers’ exemplary conduct, students’ respect for their teachers, and the control of one’s desires. The teacher–student relationship must always be directed toward devotion to Allah, making the learning process not merely a transfer of knowledge but also the cultivation of character. The implications of this research highlight that KH. Hasyim Asy’ari’s moral and spiritual principles remain highly relevant to modern education, particularly in addressing the challenges posed by the rapid development of technology and information.